Detección de factores de riesgo en un cultivo de papa a partir de mapas espaciales de calor de las variables pH y humedad sensadas a lo largo del terreno. (2021)
In this research project, it is proposed to carry out a spatial visualization (heat map) of the terrain, in which the pH and moisture variables that are present in the soil during the process of a potato crop are indicated, and thus observe how they influence the growth of the plant.